Analisis Kemampuan Problem Solving melalui Permainan Golf pada Anak Usia 5-6 Tahun - Anjarwati, Fitri; Ernawati, Ernawati; Umar, Uswatul Hasanah (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Problem-solving ability is one aspect of cognitive development in children that should be stimulated from an early age. This study was conducted to examine the problem-solving abilities of children aged 5–6 years using a golf game approach at PAUD Kuncup Melati PIKA-PKT Bontang. The study employed a descriptive qualitative research approach with nine children from Group B as research subjects. Data collection techniques included observation, interviews, and documentation. The data collected consisted of words, images, and non-numerical information. The instruments used were based on six indicators of problem-solving ability: identifying problems, gathering information, understanding and analyzing the situation, planning strategies, and evaluation. The data analysis methods used included: 1) comprehensive data collection, 2) data reduction, and 3) data presentation. The results of the descriptive analysis showed that the golf game had a positive impact on children's thinking abilities. The children actively demonstrated improved strategies in identifying problems and evaluating various scenarios from previous play sessions. The golf game helped train concentration, coordination, and decision-making, making it beneficial for developing logical, critical, and systematic thinking effectively and fundamentally. Overall, the findings of this study recommend golf games as an innovative play-based learning method that supports the comprehensive development of children’s cognitive and problem-solving abilities. Additionally, it can be integrated into the existing curriculum in early childhood education.